Selection of Superior Yeast Strains for the Fermentation of Lignocellulosic Steam-Exploded Residues - Cagnin, Lorenzo; Gronchi, Nicoletta; Basaglia, Marina; Favaro, Lorenzo; Casella, Sergio (Frontiers in Microbiology, 2021)
The production of lignocellulosic ethanol calls for a robust fermentative yeast able to tolerate a wide range of toxic molecules that occur in the pre-treated lignocellulose. The concentration of inhibitors varies according to the composition of the lignocellulosic material and the harshness of the pre-treatment used. It follows that the versatility of the yeast should be considered when selecting a robust strain. This work aimed at the validation of seven natural Saccharomyces cerevisiae strains, previously selected for their industrial fitness, for their application in the production of lignocellulosic bioethanol. Their inhibitors resistance and fermentative performances were compared to those of the benchmark industrial yeast S. cerevisiae Ethanol Red, currently utilized in the second-generation ethanol plants. The yeast strains were characterized for their tolerance using a synthetic inhibitor mixture formulated with increasing concentrations of weak acids and furans, as well as steam-exploded lignocellulosic pre-hydrolysates, generally containing the same inhibitors. Eight non-diluted liquors have been adopted to assess yeast ability to withstand bioethanol industrial conditions. The most tolerant S. cerevisiae Fm17 strain, together with the reference Ethanol Red, was evaluated for fermentative performances in two pre-hydrolysates obtained from cardoon and common reed, chosen for their large inhibitors concentrations. S. cerevisiae Fm17 outperformed the industrial strain Ethanol Red, producing up to 18 and 39 g/L ethanol from cardoon and common reed, respectively, with ethanol yields always higher than those of the benchmark strain. This natural strain exhibits great potential to be used as superior yeast in the lignocellulosic ethanol plants.